2013
DOI: 10.7589/2012-05-129
|View full text |Cite
|
Sign up to set email alerts
|

Lability in Host Defenses: Terrestrial Frogs Die from Chytridiomycosis under Enzootic Conditions

Abstract: ABSTRACT:Chytridiomycosis-induced mortalities often occur upon the emergence of Batrachochytrium dendrobatidis (Bd) in naïve amphibian populations. We report chytridiomycosis-associated mortalities in the wild of the coqui (Eleutherodactylus coqui), a declining direct-developing frog with persistent Bd infections. These findings provide additional evidence of decreased host defenses during cool-dry seasons in Puerto Rico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…data). In another study, coquis that died with high Bd loads showed signs of chytridiomycosis upon histologic examination (Longo et al 2013). Of the five Bd-exposed juveniles that survived the experiment, only one was Bd positive.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…data). In another study, coquis that died with high Bd loads showed signs of chytridiomycosis upon histologic examination (Longo et al 2013). Of the five Bd-exposed juveniles that survived the experiment, only one was Bd positive.…”
Section: Resultsmentioning
confidence: 95%
“…Analysis of capture-markrecapture data showed that the proportion of recaptured adult frogs was lower for infected adult coquis than for uninfected frogs in the Palo Colorado Forest of eastern Puerto Rico . Although populations of E. coqui persist in the wild with mild Bd infections, some individuals die from chytridiomycosis (Longo et al 2013). Vulnerability of adult coquis to Bd is thought to be affected by seasonal climatic variables, specifically, a reduced ability to resist the pathogen in cooler, drier conditions or increased transmission in a limited number of humid retreat sites .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of collection, the frogs were swabbed for the pre sence of Bd by standard methods (Longo et al 2013), and 8/24 (33%) were positive by PCR, with a mean infection intensity of 618.5 (range: 1−4888) Bd zoospore genomic equivalents. The skin secretions were enriched for hydrophobic peptides by passage over C-18 Sep-Paks (Waters) and examined by matrix-assisted laser desorption/ionization time-offlight (MALDI-TOF) mass spectrometry as previously described (Rollins-Smith et al 2006, Woodhams et al 2006b.…”
mentioning
confidence: 99%
“…In spite of an average Bd prevalence of 43% among highland populations, E. coqui survive with low to moderate infection intensities averaging 1003 Bd zoospore genomic equivalents, a pattern indicative of enzootic conditions . However, the fact that these frogs die from chytridiomycosis when environmental conditions are harsh both in the lab and in the wild suggests that they are susceptible to Bd (Longo et al , 2013, and that a mechanism to resist high infections is effective during favorable times. Thus, E. coqui is an excellent model to study the evolution of defense and how environmental factors may modulate the processes involved.…”
mentioning
confidence: 99%